A mobile differential absorption lidar to measure sub-hourly fluctuation of tropospheric ozone profiles in the Baltimore–Washington, D.C. region - J. T. Sullivan; T. J. McGee; G. K. Sumnicht; L. W. Twigg; R. M. Hoff (Atmospheric Measurement Techniques, 2014)
Tropospheric ozone profiles have been retrieved from the new ground-based National Aeronautics and Space Administration (NASA) Goddard Space Flight Center TROPospheric OZone DIfferential Absorption Lidar (GSFC TROPOZ DIAL) in Greenbelt, MD (38.99° N, 76.84° W, 57 m a.s.l.), from 400 m to 12 km a.g.l. Current atmospheric satellite instruments cannot peer through the optically thick stratospheric ozone layer to remotely sense boundary layer tropospheric ozone. In order to monitor this lower ozone more effectively, the Tropospheric Ozone Lidar Network (TOLNet) has been developed, which currently consists of five stations across the US. The GSFC TROPOZ DIAL is based on the DIAL technique, which currently detects two wavelengths, 289 and 299 nm, with multiple receivers. The transmitted wavelengths are generated by focusing the output of a quadrupled Nd:YAG laser beam (266 nm) into a pair of Raman cells, filled with high-pressure hydrogen and deuterium, using helium as buffer gas. With the knowledge of the ozone absorption coefficient at these two wavelengths, the range-resolved number density can be derived. An interesting atmospheric case study involving the stratospheric–tropospheric exchange (STE) of ozone is shown, to emphasize the regional importance of this instrument as well as to assess the validation and calibration of data. There was a low amount of aerosol aloft, and an iterative aerosol correction has been performed on the retrieved data, which resulted in less than a 3 ppb correction to the final ozone concentration. The retrieval yields an uncertainty of 16–19% from 0 to 1.5 km, 10–18% from 1.5 to 3 km, and 11–25% from 3 to 12 km according to the relevant aerosol concentration aloft. There are currently surface ozone measurements hourly and ozonesonde launches occasionally, but this system will be the first to make routine tropospheric ozone profile measurements in the Baltimore–Washington, D.C. area.